Tick Salivary Compounds for Targeted Immunomodulatory Therapy - Aounallah, Hajer; Bensaoud, Chaima; M’ghirbi, Youmna; Faria, Fernanda; Chmelar̆, Jindr̆ich; Kotsyfakis, Michail (Frontiers in Immunology, 2020)
Immunodeficiency disorders and autoimmune diseases are common, but a lack of effective targeted drugs and the side-effects of existing drugs have stimulated interest in finding therapeutic alternatives. Naturally derived substances are a recognized source of novel drugs, and tick saliva is increasingly recognized as a rich source of bioactive molecules with specific functions. Ticks use their saliva to overcome the innate and adaptive host immune systems. Their saliva is a rich cocktail of molecules including proteins, peptides, lipid derivatives, and recently discovered noncoding RNAs that inhibit or modulate vertebrate immune reactions. A number of tick saliva and/or salivary gland molecules have been characterized and shown to be promising candidates for drug development for vertebrate immune diseases. However, further validation of these molecules at the molecular, cellular, and organism levels is now required to progress lead candidates to clinical testing. In this paper, we review the data on the immuno-pharmacological aspects of tick salivary compounds characterized in vitro and/or in vivo and present recent findings on non-coding RNAs that might be exploitable as immunomodulatory therapies.